Deep Genome Resequencing Reveals Artificial and Natural Selection for Visual Deterioration, Plateau Adaptability and High Prolificacy in Chinese Domestic Sheep - Wang, Weimin; Zhang, Xiaoxue; Zhou, Xiang; Zhang, Yangzi; La, Yongfu; Zhang, Yu; Li, Chong; Zhao, Youzhang; Li, Fadi; Liu, Bang; Jiang, Zhihua (Frontiers in Genetics, 2019)
Sheep were one of the earliest domesticated animals. Both artificial and natural selection during domestication has resulted in remarkable changes in behavioral, physiological, and morphological phenotypes; however, the genetic mechanisms underpinning these changes remain unclear, particularly for indigenous Chinese sheep. In the present study, we performed pooled whole-genome resequencing of 338 sheep from five breeds representative of indigenous Chinese breeds and compared them to the wild ancestors of domestic sheep (Asian mouflon, Ovis orientalis) for detection of genome-wide selective sweeps. Comparative genomic analysis between domestic sheep and Asian mouflon showed that selected regions were enriched for genes involved in bone morphogenesis, growth regulation, and embryonic and neural development in domestic sheep. Moreover, we identified several vision-associated genes with funtional mutations, such as PDE6B (c.G2994C/p.A982P and c.C2284A/p.L762M mutations), PANK2, and FOXC1/GMSD in all five Chinese native breeds. Breed-specific selected regions were determined including genes such as CYP17 for hypoxia adaptability in Tibetan sheep and DNAJB5 for heat tolerance in Duolang sheep. Our findings provide insights into the genetic mechanisms underlying important phenotypic changes that have occurred during sheep domestication and subsequent selection.